2022
DOI: 10.3389/fimmu.2022.833635
|View full text |Cite
|
Sign up to set email alerts
|

Halophilic Archaea Halorhabdus Rudnickae and Natrinema Salaciae Activate Human Dendritic Cells and Orient T Helper Cell Responses

Abstract: Halophilic archaea are procaryotic organisms distinct from bacteria, known to thrive in hypersaline environments, including salt lakes, salterns, brines and salty food. They have also been identified in the human microbiome. The biological significance of halophiles for human health has rarely been examined. The interactions between halophilic archaea and human dendritic cells (DCs) and T cells have not been identified so far. Here, we show for the first time that the halophilic archaea Halorhabdus rudnickae a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…Halorhabdus utahensis, a member of the Halorhabdus genus, can metabolize and produce carotenoids, which have antioxidant properties [27]. Halorhabdus rudnickae has been shown to activate human dendritic cells and orient T helper cell responses [28]. Additionally, metabolites secreted by Halorhabdus rudnickae exhibit significant toxic effects on ovarian cancer cells, suggesting that it plays a protective role as an archaeon [29].…”
Section: Discussionmentioning
confidence: 99%
“…Halorhabdus utahensis, a member of the Halorhabdus genus, can metabolize and produce carotenoids, which have antioxidant properties [27]. Halorhabdus rudnickae has been shown to activate human dendritic cells and orient T helper cell responses [28]. Additionally, metabolites secreted by Halorhabdus rudnickae exhibit significant toxic effects on ovarian cancer cells, suggesting that it plays a protective role as an archaeon [29].…”
Section: Discussionmentioning
confidence: 99%
“…salaciae [19]. We chose these two strains because their genome sequences have been determined (accessible at GenBank assembly under the number GCA_900880625.1 and GCA_900110865.1, respectively), and we had already characterized their interaction with innate immune cells [20]. The metabolites of these strains were active on three ovarian cancer cell lines frequently used to study ovarian carcinoma: the cisplatin-sensitive ovarian tumor cell line A2780 and the corresponding cisplatin-resistant A2780cis cell line, as well as the cisplatin-resistant and highly invasive SK-OV-3 cell line, originating from ascites [21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…Extremophiles in the microbiome are not just niche novelties. Krawczyk et al [128] showed that the halophilic archaea Halorhabdus rudnickae and Natrinema salaciae (which are related to those found in our own microbiome) are able to work through dendritic cells to provide immunoregulation of T cell responses producing a balanced cytokine profile. These findings suggest that similar halophilic archaea may provide a useful function in the human gut.…”
Section: Copyright© Rodney R Dietertmentioning
confidence: 92%
“…Table 4 [123][124][125][126][127][128][129][130][131][132][133][134][135][136][137][138][139][140][141][142] illustrates two fundamental principles about our connection to microbes: 1) We are intimately connected to Earth's microbes, 2) Even if much of our microbiome has some stability, we are constantly exchanging microbes, microbial genes, physiologically-modifying chemicals, and gathering information from and sharing information with the microbes beyond our body. The human body is open to the environment.…”
Section: Connecting To the Iom Via Meditation Embodied Cognition And ...mentioning
confidence: 99%
See 1 more Smart Citation